Cancer Stem Cell-Based Models of Colorectal Cancer Reveal Molecular Determinants of Therapy Resistance. (8th March 2016) - De Angelis, Maria Laura; Zeuner, Ann; Policicchio, Eleonora; Russo, Giorgio; Bruselles, Alessandro; Signore, Michele; Vitale, Sara; De Luca, Gabriele; Pilozzi, Emanuela; Boe, Alessandra; Stassi, Giorgio; Ricci-Vitiani, Lucia; et al.
Abstract : Colorectal cancer stem cell (CSC)-enriched cultures were obtained efficiently from primary tumor specimens by optimizing a CSC-isolation protocol. Based on in vitro and in vivo validation, genetic characterization, and drug sensitivity analysis, panels of CSC lines were generated with defined patterns of genetic mutations and therapy sensitivity. An analysis of CSC response to EGFR-targeted therapy in vivo and an overview of factors implicated in therapy response/resistance are presented. Abstract: : Colorectal cancer (CRC) therapy mainly relies on the use of conventional chemotherapeutic drugs combined, in a subset of patients, with epidermal growth factor receptor [EGFR]-targeting agents. Although CRC is considered a prototype of a cancer stem cell (CSC)-driven tumor, the effects of both conventional and targeted therapies on the CSC compartment are largely unknown. We have optimized a protocol for colorectal CSC isolation that allowed us to obtain CSC-enriched cultures from primary tumor specimens, with high efficiency. CSC isolation was followed by in vitro and in vivo validation, genetic characterization, and drug sensitivity analysis, thus generating panels of CSC lines with defined patterns of genetic mutations and therapy sensitivity. Colorectal CSC lines were polyclonal and maintained intratumor heterogeneity in terms of somatically acquired mutations and differentiation state. Such CSC-enriched cultures were used to investigate the effects of both conventional and targeted therapies on the CSC compartment in vivo and to generate a proteomic picture of signaling pathways implicated in sensitivity/resistance to anti-EGFR agents. We propose CSC lines as a sound preclinical framework to test the effects of therapies in vitro and in vivo and to identify novel determinants of therapy resistance. Significance: Colorectal cancer stem cells (CSCs) have been shown to be responsible for tumor propagation, metastatic dissemination, and relapse. However, molecular pathways present in CSCs, as well as mechanisms of therapy resistance, are mostly unknown. Taking advantage of genetically characterized CSC lines derived from colorectal tumors, this study provides an extensive analysis of CSC response to EGFR-targeted therapy in vivo and an overview of factors implicated in therapy response or resistance. Furthermore, the implementation of a biobank of molecularly annotated CSC lines provides an innovative resource for future investigations in colorectal cancer.